2017
DOI: 10.1080/1331677x.2017.1314820
|View full text |Cite
|
Sign up to set email alerts
|

A social marketing perspective on road freight transportation of fresh fruits and vegetables: a Slovene case

Abstract: With the large increase in transportation over the last decades and the associated negative impacts upon the environment and society, a more sustainable use of transport is a crucial policy issue. This analysis focuses on road freight transport of selected produce (carrots, cabbage, apples and pears) with the aim to appraise the sustainability of road freight transport of these for the Slovene market. To this end, we take into account self-sufficiency, import and export features, transport needs, produce origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The first hypothesis stated that social innovation capability would have a positive influence on the social marketing achievements and was supported. Social innovation may help social enterprises to improve their performance (Lundvall, 2010) and it is required to develop an effective marketing strategy in order to adopt new behaviors (Bonča et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first hypothesis stated that social innovation capability would have a positive influence on the social marketing achievements and was supported. Social innovation may help social enterprises to improve their performance (Lundvall, 2010) and it is required to develop an effective marketing strategy in order to adopt new behaviors (Bonča et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It refers to a process that applies marketing principles and techniques to create, communicate, and deliver value in order to influence behaviors of the target audience aiming to benefit society (Kotler & Lee, 2008). Achieving voluntary change to adopt new attitudes, beliefs, values or behaviors in primary audiences requires a social innovation platform connected to the marketing strategy with the purpose of persuading individuals to adopt new behaviors (Bonča, Udovč, & Rodela, 2017). It is possible to assume that social innovation in its different manifestations, including innovations in social marketing itself, can contribute to obtaining better results in the achievements of social marketing.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…High pricing can lower demand (K. . Fixed pricing does not have to be continuous and long-term, but at certain times, for example, non-holiday pricing is cheaper, this dynamic pricing will be efficient (Cao et al, 2023), combining with discount prices is also more efficient in closing the shortage of visitors, if it continues, it can be done with social marketing to promote sustainability (Bonča et al, 2017), for example in the sector, food is always associated with tradition. as well as sensory properties and health (Bryła, 2015).…”
Section: Nostalgia Marketing To Premium Pricementioning
confidence: 99%
“…Because without a sound infrastructure system, the fruits of economic growth cannot be reached in every part of the economy (Babatunde, 2018). It is generally observed that the transport sector has grown to a greater extent (Bonca et al , 2017).…”
Section: Introductionmentioning
confidence: 99%